Practical prescriptions for governing fragmented governments. (30th April 2018) - Swann, William L; Kim, Seo Young
Abstract : Fragmentation of authority creates dilemmas in governance in which an individual authority's incentives are misaligned with collective interests. Such dilemmas hinder progress towards solving complex societal problems and improving service delivery, but policy research has failed to lead to a development of actionable prescriptions for dealing with them from an institutional perspective. This article draws practical lessons and theoretical propositions from the Institutional Collection Action (ICA) literature to help policymakers and scholars better understand how semiautonomous authorities overcome barriers to collective action and reduce the risk and uncertainty of collaborative arrangements across different scales of governance and institutional contexts.